Swingers [videorecording (DVD)] - Liman, Doug; Favreau, Jon; Favreau, Jon; Favreau, Jon; Vaughn, Vince; Livingston, Ron; Van Horn, Patrick; Désert, Alex, 1968-; Graham, Heather, 1970- (Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 1999)
Hip and hilarious look at a fun group of friends who spend their days looking for work and their nights hanging out in Hollywood's coolest after-hours spots.